The Workforce of Clientelism: The Case of Local Officials in the Party Machine - Ajay Shenoy; Laura V. Zimmermann (Global Labor Organization (GLO), 2021)
Local politicians can function as crucial intermediaries between voters and party bosses in a clientelistic network. We study their role by matching data on 300 million welfare payments in the Indian state of West Bengal to village-level election returns. Local politicians systematically misallocate resources based on party loyalty and successfully deliver votes to their national co-partisans. Politicians are compensated for successful mobilization through a performance bonus immediately after the national election. The (promise of) increased compensation from government funds induces opposition candidates to switch to the ruling party in strategically important local councils, bringing them under its control.
Keywords: D72; D73; H53; 330